Trace elements in sedimentary pyrite track redox and nutrient fluctuations in the Ediacaran/Cambrian Bambuí Group, Brazil - Lima, Matheus F. de; Caxito, Fabrício A.; Large, Ross; Mukherjee, Indrani; Uhlein, Gabriel J.; Hippertt, João Pedro T.M.; Moura, Samuel A.; Okubo, Juliana [UNESP]; Warren, Lucas [UNESP] (Elsevier, 2023)
We apply trace element analysis of syn-sedimentary pyrite to track the redox and nutrient variations in the Ediacaran-Cambrian Bambuí Group of eastern Brazil. Sedimentary pyrite from black shales interleaved within the basal cap carbonate of the 635–600 Ma Pedro Leopoldo Member, deposited in an open marine setting connected to the global sea, preserve high Mo up to >200 ppm, erratic enrichment of micronutrients such as Cu, Ni, Ba, Zn and uniform enrichment of Se. This indicates the importance of oxidative continental weathering and development of an enhanced Redox Sensitive Elements (RSE) dissolved reservoir on the aftermath of the Marinoan glaciation, with atmospheric O2 levels, calculated from Se/Co ratios of pyrites, around 2.5–3.5 wt%. A shallow oxic layer over deep euxinic realms made possible by high concentrations of dissolved sulfate was probably maintained up to the late Ediacaran, during deposition of the Cloudina-bearing Lagoa Santa Member (585–540 Ma). Upsection, however, radical shifts to muted Mo concentrations and overall low micronutrient concentrations are recorded in the Serra de Santa Helena Formation, with O2 levels plunging below 1 wt%. This indicates the development of ferruginous bottom water conditions in a sulfate-poor setting, due to restriction of the basin by the encircling Brasiliano mountains that formed Gondwana. The restricted, oxygen-poor and nutrient-depleted conditions caused the demise of complex life forms and hampered the development of typical Ediacaran-Cambrian ecosystems. Basin re-connection might have occurred during deposition of the Lagoa do Jacaré Formation, with independent proxies such as local tidal facies indicating a return to more ventilated conditions in the upper Bambuí Group. Our results highlight the importance of basin restriction and connection over coupled redox-nutrients variations during the development of Ediacaran-Cambrian ecosystems.
Keywords: Atmosphere oxygenation; Gondwana; Redox-sensitive elements; Sedimentary pyrite